IMPLEMENTASI KEBIJAKAN PEMBANGUNAN BERPERSPEKTIF GENDER DI PROVINSI RIAU TAHUN 2021-2022 - Saputra, Difki; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Gender Perspective Development Policy in Riau Province is a development concept that pays attention to gender equality in every aspect of life. Implementation of development policies with a gender perspective in Riau Province refers to an approach that pays attention to equal rights and opportunities between women and men in every policy, program and development activity in the area. The Riau Provincial Government has issued Riau Province Governor Regulation Number 18 of 2018 concerning Guidelines for Implementing Gender Mainstreaming in Riau Province. This is to minimize gender gaps. The aim of this research is to describe and analyze the implementation of development policies with a gender perspective in Riau Province in 2021-2022. This research was conducted at the Research and Development Regional Development Planning Agency (Bappedalitbang) and the Office of Women's Empowerment and Child Protection, Population Control and Family Planning (DP3AP2KB) of Riau Province. This research uses a qualitative approach with descriptive methods. In collecting data the author used interview and documentation techniques. The results of this research can be concluded that the implementation of development policies with a gender perspective in Riau Province has not been optimal. Even though several policies have been implemented, not all Regional Apparatus Organizations (OPD) in Riau Province are implementing Gender Perspective Development policies and the Implementation of Gender Mainstreaming (PUG) in the Region is still slow. Through Gender Responsive Budgeting Planning (PPRG) which is ongoing and can be seen in the Gender Development Index (IPG) for Riau Province in 2021 of 88,38 and in 2022 of 88,71 still below the National Rank, namely in 2021 it was 91,27 and In 2022 it will be 91,63. . Keywords: Policy Implementation, Gender, Development